Rolling warrior : the incredible, sometimes awkward, true story of a rebel girl on wheels who helped spark a revolution - Heumann, Judith E.; Joiner, Kristen (Beacon Press, 2021)
After contracting polio as a baby in 1949 and being confined to a wheelchair, six-year-old Judith Heumann was told she couldn't attend school because she was a fire hazard. From then on, Judith had an uphill battle fighting for her rights in a world created for humans who can walk. In this memoir, Judith describes her journey of being cast aside and ignored and how she used her unstoppable energy to get politicians to hear the voices of the disabled.